Analysis of Connectedness to Nature of Individuals Who Do Physical Activity at Outdoors - Övünç Erdeveciler; Velittin Balcı; Serap Aktaş; Erdem Çakaloğlu (ümit doğan üstün, 2021)
The concept of Connectedness to Nature, which has been frequently mentioned in recent years and is the most important milestone for sustainable understanding, has become the focus of various disciplines and fields of study. In this context, our study aims to contribute to the literature that will form a basis for the relationship between nature and sports by measuring the dependence of individuals who do the physical activity outdoors. The sample group of the study consists of 241 participants who come to do sports on certain days of the week in Ankara. "Connectedness to Nature Scale" adapted to Turkish by Bektaş, Kural, and Orçan, (2017) was used to determine the level of commitment to nature of the participants. The Cronbach's Alpha coefficient for the whole of the scale was found to be 88, and t-test and variance analysis methods were used to determine the dependency of the participants to nature according to their demographic information. The participants were examined, it was found that 34.9% were women and 65.1% were men. When their dependence on nature according to gender is examined, no statistically significant difference was found (t = -, 446 p> .05). When the frequency of physical activity of the participants is evaluated, doing physical activity continuously creates a positive effect on the connectedness to nature. As a result, as the amount of physical activities increases in open areas, the connectedness to nature will increase.